ECtHR Practice of Resolving Disputes on Royalty Taxation for the Use of Copyright Objects - Суханова, Дар'я Сергіївна; Суханова, Д. С.; Суханова, Дарья Сергеевна; Sukhanova, Daria S.; Цуркану, Сюзанна Іванівна; Цуркану, С. І.; Цуркану, Сюзанна Ивановна; Tsurkanu, Siuzanna I.; Еннан, Руслан Євгенович; Еннан, Р. Є.; Эннан, Руслан Евгеньевич; Ennan, Ruslan Ye.; et al. (ASERS Publishing, 2019)
The European Court of Human Rights is increasingly focusing on the compatibility of tax law and intellectual property law with European standards of human rights and fundamental freedoms in the relationship between tax authorities and taxpayers. To increase the efficiency of the work of the bodies of the State Tax Service of Ukraine, as well as the judicial authorities of Ukraine and to ensure an adequate level of protection of the rights and interests of individuals and legal entities, it is important to analyze the ECtHR's practice of resolving royalties for the use of copyright objects. The research methodology consists of general theoretical and special scientific methods, namely: dialectical, historical, systemic, modeling and abstraction, induction, deduction, analysis, synthesis, comparative-legal method, and theoretical modeling. The study analyzes the ECtHR's practice of the settlement of disputes on royalty taxation for the use of copyright objects, clarifies the grounds and key positions of the European Court of Human Rights for resolving disputes related to royalty taxation, and reveals the value of the case-law of the European Court of Human Rights in the development of the tax system of Ukraine.

Європейський суд з прав людини все більше акцентує увагу на сумісності податкового законодавства та права інтелектуальної власності з європейськими стандартами прав людини та основних свобод у відносинах між податковими органами та платниками податків. Для підвищення ефективності роботи органів Державної податкової служби України, а також органів юстиції України та забезпечення належного рівня захисту прав та інтересів фізичних та юридичних осіб важливим є аналіз практики ЄСПЛ щодо врегулювання роялті за використання об’єктів авторського права. Методологія дослідження складається із загальнотеоретичних та спеціальнонаукових методів, а саме: діалектичного, історичного, системного, моделювання та абстракції, індукції, дедукції, аналізу, синтезу, порівняльно-правового методу та теоретичного моделювання. У дослідженні проаналізовано практику ЄСПЛ щодо вирішення спорів щодо оподаткування роялті за використання об’єктів авторського права, з’ясовуються підстави та ключові позиції Європейського суду з прав людини щодо вирішення спорів, пов’язаних з оподаткуванням роялті, розкривається значення справи – право Європейського суду з прав людини у розвитку податкової системи України.
Sukhanova D. ECtHR Practice of Resolving Disputes on Royalty Taxation for the Use of Copyright Objects / D. Sukhanova, S. Tsurkanu, R. Ennan, O. Balatska, L. Strelbitska // Journal of Advanced Research in Law and Economics. – Vol. 10. - № 7(45). - ASERS Publishing, 2019. – P. 2113-2121.
Keywords: tax law; ECtHR decisions; royalties; payment; intellectual property; income tax; value added tax; податкове законодавство; рішення ЄСПЛ; роялті; оплата; інтелектуальна власність; податок на прибуток; податок на додану вартість; Research Subject Categories::LAW/JURISPRUDENCE